Aspergilli and their aflatoxins contamination of poultry and animal feedstuff samples in western region of Saudi Arabia - A. Gherbawy, Youssuf; M. Shebany, Yassmin; Alharthy, Helal (Penerbit Universiti Kebangsaan Malaysia, 2019)
Aspergillus and their aflatoxins contaminations were studied in sixty poultry and animal feedstuff samples collected from the western region (Jeddah, Makkah and Taif cities) from Saudi Arabia. Fourteen species of Aspergillus were isolated and identified in the present investigation using Potato Dextrose Agar (PDA) at 27ºC. The identification of isolated Aspergillus was confirmed by using internal transcribed spacer (ITS) region sequencing for representative species (194 species) of the collected Aspergillus sp. were sequenced and the obtained sequence results were deposited in Gene Bank under accession numbers. The sequence results indicated to the full correspondence between the molecular identification of the isolated fungi and the morphological identification. Moisture content was considered indicator for the number of Aspergillus isolated, therefore, Aspergillus and their aflatoxins were isolated in high counts from Jeddah and Taif according to the moisture content. Therefore, A. flavus was the most common species (59.78%), followed by A. niger (21.59%). The co-occurrence of Aspergillus species ranged from one species to 6 species per sample. The frequencies of occurrence for most afltoxigenic species isolated from studied samples ranged from 2 to 56%. Aspergillus flavus contaminated the majority of investigated feedstuff samples and the co-occurrence of more than one aflatoxigenic species was reported in many samples.